Pendidikan Karakter Berbasis Ekologis dalam Novel Anak-Anak Sungai Sondong Karya Ramajani Sinaga dan Implikasinya pada Pembelajaran Sastra di Sekolah - Baiq Rizki Hidayati; Hadiatul Rodiyah (Universitas Hamzanwadi, 2024)
This research aims to describe the value of ecologically based character education in the novel Anak-anak Sungai Sondong by Ramajani Sinaga, and implications for Literature Learning in Schools. This research method is qualitative research. The data source for this research uses primary and secondary data. Primary data uses the novel Sondong Children. Secondary data was obtained from journals and books related to character education with an environmental ethics approach. Data collection techniques use reading and note-taking techniques. Data analysis techniques using triangulation, reduction, presentation and concluding data. The results of this research are (a) responsibility, (b) love and concern for nature, (c) solidarity, (d) respect for nature, (e) living simply and in harmony with nature, (f) justice. From the results of data analysis, there are 89-character education with an environmental ethics approach that can be implemented in literature learning in schools in accordance with the dimensions of the Pancasila profile, namely morals towards nature.